Sherds on the Edge: Characterization of 16th Century Colonial Spanish Pottery Recovered from the Solomon Islands. (7th July 2015) - Kelloway, S. J.; Ferguson, T. J.; Iñañez, J. G.; Vanvalkenburgh, P.; Roush, C. C.; Gibbs, M.; Glascock, M. D.
Abstract : We present the results of instrumental neutron activation analysis of ceramics recovered from the Solomon Islands, associated with Alvaro de Mendaña y Neira's 16th century colonizing expedition to the region (c.1595–6). Based on the chemical and typological data and previously published petrological and geochronological research, this study assigns the provenance of the ceramics variously to Peru, Panama, Spain, China and Thailand. A comparison of the provenance results with historical records related to Mendaña's voyage also shows the value of the archaeological assemblage in providing a detailed picture of provisioned ceramic types and their provenance.